Silicon-carbon composite material, preparation method thereof, negative pole piece, secondary battery and device

By using carbon matrix with pore structure and silicon-carbon composite materials with phosphorus doped elements in lithium-ion batteries, the problems of high expansion and poor conductivity of silicon-based materials in lithium-ion batteries are solved, and better cycling performance and energy density are achieved.

CN119833581APending Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311728656.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Silicon-based materials have high expansion characteristics and poor conductivity in lithium-ion batteries, resulting in the structure powderization and disengagement of the current collector during the charging and discharging of the battery, affecting the energy density and cycling performance.

Method used

Using a silicon-carbon composite material, the silicon-based material is distributed in a carbon matrix with a pore structure and doped with phosphorus elements in the material to improve conductivity and alleviate silicon expansion.

Benefits of technology

It effectively alleviates the expansion problem of silicon-based materials, improves the cycling performance and conductivity of the battery, and improves the energy density of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004611536890000231
    Figure BDA0004611536890000231
  • Figure BDA0004611536890000241
    Figure BDA0004611536890000241
  • Figure HDA0004611537110000011
    Figure HDA0004611537110000011
Patent Text Reader

Abstract

The invention relates to a silicon-carbon composite material and a preparation method thereof, a negative pole piece, a secondary battery and a device, the silicon-carbon composite material comprises a carbon matrix with a pore structure and a silicon-based material distributed in the pore structure of the carbon matrix, and the silicon-carbon composite material contains phosphorus element. The silicon-based material in the silicon-carbon composite material improves the capacity of the carbon matrix, and the carbon matrix with the pore structure can be used as a buffer medium for volume expansion of the silicon-based material in the charging and discharging process while improving the conductivity of the silicon-based material, so that the problem that the volume of the secondary battery is increased due to silicon expansion is effectively relieved; and the phosphorus element doped in the skeleton of the carbon matrix is beneficial to improving the electronic conductivity of the material, so that the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a silicon-carbon composite material and a preparation method thereof, a negative electrode sheet, a secondary battery and a device. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] In recent years, as the application scope of lithium-ion batteries becomes wider and wider, lithium-ion batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the continuous development of lithium-ion battery technology, users have put forward higher and higher requirements for the energy density of lithium-ion batteries. Silicon-based materials are widely used in lithium-ion batteries due to their high capacity, but due to the high expansion characteristics of silicon-based materials, the silicon-based material structure is powdered during the battery charging and discharging process, and it loses its activity due to separation from the current collector, and the conductivity of silicon-based materials is poor. Therefore, while silicon-based materials improve the energy density of lithium-ion batteries, they will also affect the cycle performance of secondary batteries, limiting the further development of lithium-ion battery technology. Summary of the invention

[0004] The present application provides a silicon-carbon composite material and a preparation method thereof, a negative electrode plate, a secondary battery and a device to alleviate the expansion of silicon-based materials and improve the cycle performance of the battery.

[0005] In order to achieve the above object, the first aspect of the present application provides a silicon-carbon composite material, comprising:

[0006] a carbon matrix having a porous structure; and

[0007] A silicon-based material distributed in the pore structure of the carbon matrix;

[0008] The silicon-carbon composite material contains phosphorus element.

[0009] Therefore, the silicon-based material in the silicon-carbon composite material of the present application improves the capacity of the carbon matrix, and the carbon matrix with a pore structure not only improves the conductivity of the silicon-based material, but also can serve as a buffer medium for the volume expansion of the silicon-based material during the charging and discharging process, effectively alleviating the problem of the increase in volume of the secondary battery due to silicon expansion; and the phosphorus element contained in the silicon-carbon composite material helps to improve the electronic conductivity of the material, thereby improving the cycle performance of the silicon-carbon composite material.

[0010] In some embodiments, the mass proportion of the phosphorus element in the silicon-carbon composite material is 5ppm-80ppm; optionally 10ppm-50ppm.

[0011] In some embodiments, the silicon-carbon composite material further contains at least one of aluminum and potassium.

[0012] Optionally, the silicon-carbon composite material further contains aluminum, and the mass proportion of phosphorus in the silicon-carbon composite material is greater than the mass proportion of aluminum in the silicon-carbon composite material;

[0013] Optionally, the silicon-carbon composite material further contains potassium element, and the mass proportion of phosphorus element in the silicon-carbon composite material is greater than the mass proportion of potassium element in the silicon-carbon composite material.

[0014] Optionally, the silicon-carbon composite material further contains aluminum and potassium, and the mass proportion of the aluminum in the silicon-carbon composite material is smaller than the mass proportion of the potassium in the silicon-carbon composite material.

[0015] Optionally, the silicon-carbon composite material further contains aluminum element, and the mass proportion of the aluminum element in the silicon-carbon composite material is 5ppm-80ppm; optionally 10ppm-40ppm.

[0016] Optionally, the silicon-carbon composite material further contains potassium element, and the mass proportion of the potassium element in the silicon-carbon composite material is 5ppm-80ppm; optionally 10ppm-70ppm.

[0017] In some embodiments, the silicon-based material has one or more of the following features:

[0018] (1) The grain size of the silicon-based material is ≤8nm, and may be ≤5nm, and may be 1nm-4nm;

[0019] (2) The silicon-based material includes one or more of silicon, silicon-oxygen compounds, silicon-carbon compounds or silicon alloys;

[0020] (3) The shape of the silicon-based material includes one or more of spherical, quasi-spherical, flake and linear.

[0021] In some embodiments, the carbon matrix has one or more of the following characteristics:

[0022] (1) The average pore size of the pore structure is 0.5 nm-8 nm, and can be 0.5 nm-5 nm;

[0023] (2) The pore structure includes micropores, and the average pore diameter d1 of the micropores satisfies: 0.5 nm ≤ d1 < 2 nm;

[0024] (3) The pore structure includes mesopores, and the average pore diameter d2 of the mesopores satisfies: 2nm≤d2≤8nm;

[0025] (4) The pore structure includes micropores, and the number of the micropores in the pore structure accounts for 60%-90%, and can be 70%-80%;

[0026] (5) The specific surface area of ​​the carbon matrix is ​​500 m 2 / g-2000m 2 / g, optional 1000m 2 / g-1800m 2 / g.

[0027] In some embodiments, the silicon-carbon composite material has one or more of the following characteristics:

[0028] (1) The volume distribution particle size Dv50 of the silicon-carbon composite material is 3 μm-15 μm, and can be optionally 5 μm-12 μm;

[0029] (2) The volume distribution particle size Dv90 of the silicon-carbon composite material is ≤35 μm, which can be selected to be 15 μm-25 μm;

[0030] (3) The particle size distribution of the silicon-carbon composite material satisfies: 1≤(Dv90-Dv10) / Dv50≤3, which may be 1≤(Dv90-Dv10) / Dv50≤2;

[0031] (4) The specific surface area of ​​the silicon-carbon composite material is 1 m 2 / g-10m 2 / g, optional 2m 2 / g-6m 2 / g;

[0032] (5) The tap density of the silicon-carbon composite material is 0.8 g / cm 3 -1.2g / cm 3 , optional 0.85g / cm 3 -1.0g / cm 3 ;

[0033] (6) The powder resistivity of the silicon-carbon composite material at 16 MPa is ≤5Ω·cm, and can be ≤2Ω·cm;

[0034] (7) The mass proportion of silicon element in the silicon-carbon composite material is 20%-60%, and can be optionally 30%-50%.

[0035] In some embodiments, at least a portion of the surface of the silicon-carbon composite material has a coating layer; optionally, the coating layer is a carbon coating layer.

[0036] In some embodiments, the carbon coating layer has one or more of the following characteristics:

[0037] (1) The material of the carbon coating layer includes amorphous carbon;

[0038] (2) The thickness of the carbon coating layer is 50nm-200nm.

[0039] In some embodiments, the phosphorus element is distributed in the carbon matrix; and / or at least one of the aluminum element and the potassium element is distributed in the carbon matrix.

[0040] The second aspect of the present application provides a method for preparing the silicon-carbon composite material of the first aspect of the present application, comprising the following steps:

[0041] The carbon material precursor is mixed with a phosphorus-containing compound and sintered to prepare a carbon matrix with a porous structure;

[0042] The silicon-based material is deposited in the pore structure of the carbon matrix to prepare the silicon-carbon composite material.

[0043] The method for preparing the silicon-carbon composite material provided in the present application has a simple process, can achieve one-step pore formation, and the obtained pore size is relatively uniform, and phosphorus elements can be incorporated into the skeleton of the carbon matrix.

[0044] In some embodiments, the mass ratio of the carbon material precursor to the phosphorus-containing compound is 100:(3-15); optionally, it can be 100:(4-10).

[0045] In some embodiments, the sintering temperature is 600°C-1000°C; optionally 600°C-900°C.

[0046] In some embodiments, the sintering time is 1 h-12 h; optionally 4 h-8 h.

[0047] In some embodiments, the conditions for preparing the carbon matrix further include one or more of the following conditions:

[0048] (1) Mixing the carbon material precursor with the phosphorus-containing compound includes mixing the carbon material precursor with a solution containing the phosphorus-containing compound;

[0049] Optionally, the carbon material precursor is mixed with a solution containing the phosphorus-containing compound and then allowed to stand;

[0050] Further optionally, the standing time is 12h-24h;

[0051] (2) the phosphorus-containing compound includes one or more of phosphoric acid, potassium phosphate, sodium phosphate, monocalcium phosphate or monopotassium phosphate;

[0052] (3) The carbon material precursor includes one or more of biomass hard carbon or resin-based carbon materials;

[0053] (4) The carbon material precursor contains at least one of aluminum and potassium;

[0054] Optionally, the carbon material precursor contains aluminum element, and the mass proportion of the aluminum element in the carbon material precursor is 5ppm-80ppm; optionally 6ppm-60ppm;

[0055] Optionally, the carbon material precursor contains potassium element, and the mass proportion of the potassium element in the carbon material precursor is 5ppm-80ppn; optionally 6ppm-60ppm;

[0056] (5) The sintering atmosphere includes one or more of an inert gas and nitrogen;

[0057] Optionally, the atmosphere of the sintering process includes one or more of argon and nitrogen.

[0058] In some embodiments, the step of depositing the silicon-based material within the pore structure of the carbon matrix comprises:

[0059] The carbon substrate is placed in a mixed gas containing a silicon source and a first protective gas, and a first vapor deposition is performed to deposit the silicon-based material in the pore structure of the carbon substrate.

[0060] Optionally, the first vapor deposition comprises one or more of the following conditions:

[0061] (1) The temperature of the first vapor deposition is 400° C.-800° C., optionally 500° C.-700° C., and more preferably 500° C.-600° C.;

[0062] (2) The time of the first vapor deposition is 1 h to 12 h, and can be 4 h to 8 h;

[0063] (3) The volume proportion of the silicon source in the mixed gas is 10%-50%;

[0064] (4) The volume proportion of the first protective gas in the mixed gas is 30%-85%;

[0065] (5) The positive difference between the pressure of the first vapor deposition and the atmospheric pressure is 200Pa-600Pa;

[0066] (6) The silicon source includes one or more of monosilane, disilane and trisilane;

[0067] (7) The first protective gas includes one or more of nitrogen and argon.

[0068] In some embodiments, the mixed gas further comprises a first carbon source;

[0069] Optionally, the volume proportion of the first carbon source in the mixed gas is 5%-20%;

[0070] Optionally, the volume ratio of the silicon source to the first carbon source is (2-10):1;

[0071] Optionally, the first carbon source includes one or more of methane, ethylene and acetylene.

[0072] In some embodiments, after the step of depositing the silicon-based material in the pore structure of the carbon matrix, the method further comprises:

[0073] Placing the carbon substrate in a mixed gas containing a second carbon source and a second protective gas, and performing a second vapor deposition to form the carbon coating layer on at least a portion of the outer surface of the carbon substrate;

[0074] Optionally, the second vapor deposition comprises one or more of the following conditions:

[0075] (1) The temperature of the second vapor deposition is 500° C.-900° C.;

[0076] (2) The second vapor deposition time is 1h-6h;

[0077] (3) the volume proportion of the second carbon source in the mixed gas is 5%-50%, and the sum of the volume proportions of the second carbon source and the second protective gas in the mixed gas is 100%;

[0078] (4) the second carbon source includes one or more of methane, ethylene and acetylene;

[0079] (5) The second protective gas includes one or more of nitrogen and argon.

[0080] The third aspect of the present application provides a negative electrode sheet, comprising:

[0081] A negative electrode current collector; and

[0082] The negative electrode active material layer is located on at least one side of the negative electrode current collector, and the negative electrode active material layer includes the silicon-carbon composite material of the first aspect of the present application or the silicon-carbon composite material prepared by the method of the second aspect of the present application.

[0083] The fourth aspect of the present application provides a secondary battery, comprising the negative electrode sheet of the third aspect of the present application.

[0084] The secondary battery of the present application comprises the silicon-carbon composite material provided by the present application and has excellent cycle performance.

[0085] A fifth aspect of the present application provides an electrical device, comprising the secondary battery of the fourth aspect of the present application.

[0086] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery.

[0087] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0089] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0090] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0091] Figure 3 It is a schematic diagram of a battery module according to one embodiment of the present application.

[0092] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application.

[0093] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0094] Figure 6 A schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.

[0095] Description of reference numerals:

[0096] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 cover plate; 6 electrical device. DETAILED DESCRIPTION

[0097] Below, some embodiments of the silicon-carbon composite material and its preparation method, negative electrode plate, secondary battery and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0098] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are also listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0099] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0100] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0101] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0102] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0103] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0104] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0105] Silicon-based materials are widely used in secondary batteries. However, due to their high expansion characteristics and poor conductivity, while silicon-based materials improve the energy density of lithium-ion batteries, they also affect the cycle performance of secondary batteries.

[0106] Based on the above problems, the present application adopts a carbon material precursor mixed with a solution containing a phosphoric acid substance and heated and sintered. The phosphoric acid substance helps to open the cell wall framework of the carbon source precursor during the sintering process, realize one-step pore formation and the obtained pore size is relatively uniform, thereby preparing a carbon matrix with a suitable pore structure; at the same time, phosphorus is doped into the skeleton of the carbon matrix, which helps to improve the electronic conductivity of the silicon-carbon composite material and enhance the cyclic performance of the material.

[0107] A first aspect of the present application provides a silicon-carbon composite material, comprising a carbon matrix having a pore structure and a silicon-based material distributed in the pore structure of the carbon matrix, wherein the silicon-carbon composite material contains phosphorus.

[0108] It should be noted that the carbon matrix mentioned above refers to a carbon-based material having a pore structure on its outer surface and / or inside, and the number of pore structures contained in the carbon matrix may be 1 or more.

[0109] The silicon-carbon composite material includes a silicon-based material distributed in the pore structure of a carbon matrix, and may also include a silicon-based material distributed on the surface of a support of the carbon matrix.

[0110] It can be understood that the silicon-carbon composite material of the present application includes a carbon matrix with a pore structure and a silicon-based material distributed in the pore structure. The silicon-based material improves the capacity of the carbon matrix, and the carbon matrix with a pore structure improves the conductivity of the silicon-based material, and can also serve as a buffer medium for the volume expansion of the silicon-based material during charging and discharging; and the phosphorus element contained in the silicon-carbon composite material helps to improve the electronic conductivity of the material, thereby improving the cycle performance of the battery.

[0111] In some embodiments, the mass proportion of phosphorus in the silicon-carbon composite material is 5ppm-80ppm; for example, it can be but not limited to 3ppm, 5ppm, 10ppm, 15ppm, 20ppm, 25ppm, 30ppm, 35ppm, 40ppm, 45ppm, 50ppm, 55ppm, 60ppm, 65ppm, 70ppm, 75ppm, 80ppm or a range between any two of the above values. When the mass proportion of phosphorus in the silicon-carbon composite material is within the above range, the cycle performance of the battery can be further improved.

[0112] As an example, the mass proportion of phosphorus in the silicon-carbon composite material can be but is not limited to 10ppm-80ppm, 15ppm-80ppm, 20ppm-80ppm, 25ppm-70ppm, 30ppm-60ppm, 35ppm-50ppm, 35ppm-45ppm, 10ppm-60ppm, 10ppm-35ppm, 10ppm-45ppm, 45ppm-60ppm, 35ppm-60ppm, 35ppm-80ppm, 45ppm-80ppm, 60ppm-80ppm, 5ppm-10ppm, 5ppm-35ppm or 5ppm-45ppm, etc.

[0113] In some optional embodiments, the mass proportion of phosphorus in the silicon-carbon composite material is 10 ppm-50 ppm.

[0114] In some embodiments, at least one of aluminum and potassium is also distributed in the skeleton of the carbon matrix. Thus, the introduction of Al and / or potassium can improve the electronic conductivity of the carbon matrix, and at the same time, the Al and / or potassium doping can be used as an attractant to improve the uniformity of silicon deposition.

[0115] In some embodiments, the silicon-carbon composite material further contains aluminum element, and the mass proportion of phosphorus element in the silicon-carbon composite material is greater than the mass proportion of aluminum element in the silicon-carbon composite material.

[0116] In some embodiments, the silicon-carbon composite material further contains potassium, and the mass proportion of phosphorus in the silicon-carbon composite material is greater than the mass proportion of potassium in the silicon-carbon composite material.

[0117] In some embodiments, the silicon-carbon composite material further contains aluminum and potassium, and the mass proportion of the aluminum in the silicon-carbon composite material is less than the mass proportion of the potassium in the silicon-carbon composite material.

[0118] In some embodiments, the silicon-carbon composite material further contains aluminum, and the mass proportion of aluminum in the silicon-carbon composite material is 5ppm-80ppm; for example, it can be but not limited to 5ppm, 7ppm, 10ppm, 13ppm, 15ppm, 17ppm, 20ppm, 23ppm, 25ppm, 27ppm, 30ppm, 33ppm, 35ppm, 37ppm, 40ppm, 43ppm, 45ppm, 47ppm, 50ppm, 53ppm, 55ppm, 57ppm, 60ppm, 63ppm, 65ppm, 67ppm, 70ppm, 73ppm, 75ppm, 77ppm, 80ppm or the range between any two of the above values. When the mass proportion of aluminum in the silicon-carbon composite material is within the above range, it is beneficial to further improve the material conductivity and silicon deposition uniformity.

[0119] As an example, the mass proportion of aluminum element in the silicon-carbon composite material can be but is not limited to 5ppm-75ppm, 10ppm-70ppm, 10ppm-40ppm, 15ppm-65ppm, 20ppm-60ppm, 25ppm-55ppm, 30ppm-50ppm, 35ppm-45ppm, 10ppm-35ppm, 15ppm-30ppm or 20ppm-30ppm, etc.

[0120] In some embodiments, the silicon-carbon composite material further contains potassium, and the mass proportion of potassium in the silicon-carbon composite material is 5ppm-80ppm; for example, it can be but not limited to 5ppm, 7ppm, 10ppm, 13ppm, 15ppm, 17ppm, 20ppm, 23ppm, 25ppm, 27ppm, 30ppm, 33ppm, 35ppm, 37ppm, 40ppm, 43ppm, 45ppm, 47ppm, 50ppm, 53ppm, 55ppm, 57ppm, 60ppm, 63ppm, 65ppm, 67ppm, 70ppm, 73ppm, 75ppm, 77ppm, 80ppm or the range between any two of the above values. When the mass proportion of potassium in the silicon-carbon composite material is within the above range, it is beneficial to further improve the material conductivity and silicon deposition uniformity.

[0121] As an example, the mass proportion of potassium in the silicon-carbon composite material can be but is not limited to 5ppm-75ppm, 10ppm-70ppm, 15ppm-65ppm, 20ppm-60ppm, 25ppm-55ppm, 30ppm-50ppm, 35ppm-45ppm, 10ppm-35ppm, 15ppm-40ppm or 20ppm-35ppm, etc.

[0122] The mass proportions of various elements (such as silicon, phosphorus, aluminum or potassium) mentioned in this application in the silicon-carbon composite material can be referred to EPA-3052-1996 "Microwave Acid Digestion of Silicates" to digest the silicon-carbon composite material, and then the content of the target element is determined by using an inductively coupled plasma optical emission spectrometer (ICP-OES) in accordance with EPA 6010D-2014 "Inductively Coupled Plasma Atomic Emission Spectrometry"; for example, the ICAP-7000 inductively coupled plasma optical emission spectrometer of Thermo Fisher Scientific can be used.

[0123] As an example, the mass proportion of the above-mentioned phosphorus, aluminum or potassium in the silicon-carbon composite material can be determined by the following method: 0.5 g of the silicon-carbon composite material sample is microwave-digested with 10 mL of nitric acid and 10 mL of hydrofluoric acid, added to a 50 mL volumetric flask after digestion, and then the content of the target element is determined using ICAP-7000 ICP-OES.

[0124] In some embodiments, the grain size of the silicon-based material is ≤8nm; for example, it can be but not limited to 0.01nm, 0.05nm, 0.1nm, 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm or a range between any two of the above values. When the grain size of the silicon-based material is within the above range, the collapse of the silicon-carbon composite material structure caused by the expansion of the silicon-based material during the charge and discharge cycle can be prevented. Optionally, the grain size of the silicon-based material is ≤5nm. More optionally, the grain size of the silicon-based material is 1nm-4nm.

[0125] As an example, the grain size of the silicon-based material mentioned above can be calculated using an X-ray diffraction pattern or characterized by a transmission electron microscope to obtain the grain size of the silicon-based material.

[0126] In some embodiments, the silicon-based material includes one or more of silicon alone, silicon-oxygen compounds, silicon-carbon compounds, or silicon alloys.

[0127] In some embodiments, the shape of the silicon-based material includes one or more of a sphere, a spheroid, a flake, and a wire.

[0128] In some embodiments, the average pore size of the carbon matrix pore structure is 0.5nm-8nm; for example, it can be but not limited to 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm or a range between any two of the above values. When the average pore size of the carbon matrix pore structure is within the above range, the silicon-based material deposited in the pore structure can have a relatively uniform size, reducing the probability of depositing large-sized silicon-based materials.

[0129] In some optional embodiments, the average pore size of the carbon matrix pore structure is 0.5 nm-5 nm.

[0130] In some embodiments, the pore structure includes micropores, and the average pore diameter d1 of the micropores satisfies 0.5 nm≤d1<2 nm.

[0131] In some embodiments, the pore structure includes mesopores, and the average pore diameter d2 of the mesopores satisfies: 2nm≤d2≤8nm.

[0132] In some embodiments, the pore structure includes micropores, and the number of micropores in the pore structure accounts for 60%-90%; for example, it can be but not limited to 60%, 63%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 83%, 85%, 88%, 90% or a range between any two of the above values. When the number of micropores in the pore structure accounts for within the above range, the probability of depositing large-sized silicon-based materials can be further reduced. Optionally, the number of micropores in the pore structure accounts for 70%-80%.

[0133] As an example, the average pore size of the above-mentioned carbon matrix pore structure can be measured by nitrogen adsorption and desorption method.

[0134] In some embodiments, the specific surface area of ​​the carbon substrate is 500 m 2 / g-2000m 2 / g; for example, but not limited to 500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g or the range between any two of the above values. When the specific surface area of ​​the carbon matrix is ​​within the above range, it is beneficial for the silicon-based material to be deposited in the pore structure of the carbon matrix, and at the same time, it can avoid excessive deposition of the silicon-based material, thereby avoiding the collapse of the carbon matrix caused by excessive volume expansion of the silicon-based material during the charge and discharge cycle.

[0135] In some optional embodiments, the specific surface area of ​​the carbon matrix is ​​1000 m 2 / g-1800m 2 / g.

[0136] As an example, the specific surface area of ​​the carbon matrix mentioned above can be measured by nitrogen adsorption and desorption method.

[0137] In some embodiments, the volume distribution particle size Dv50 of the silicon-carbon composite material is 3μm-15μm; when the volume distribution particle size Dv50 of the silicon-carbon composite material is in the above range, it is conducive to the uniform deposition of the silicon-based material in the carbon matrix, and the secondary battery kinetics is better. As an example, the volume distribution particle size Dv50 of the silicon-carbon composite material mentioned above can be but is not limited to 3μm, 5μm, 7μm, 10μm, 12μm, 15μm or a range between any two of the above values.

[0138] In some optional embodiments, the volume distribution particle size Dv50 of the silicon-carbon composite material is 5 μm-12 μm.

[0139] In some embodiments, the volume distribution particle size Dv90 of the silicon-carbon composite material is ≤35 μm; for example, it can be but not limited to 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, or a range between any two of the above values. When the volume distribution particle size Dv90 of the silicon-carbon composite material is within the above range, the probability of the negative electrode plate piercing the diaphragm can be reduced.

[0140] In some optional embodiments, the volume distribution particle size Dv90 of the silicon-carbon composite material is 15 μm-25 μm.

[0141] In some embodiments, the particle size distribution of the silicon-carbon composite material satisfies: 1≤(Dv90-Dv10) / Dv50≤3. When the particle size distribution of the silicon-carbon composite material satisfies the above relationship, it is beneficial to improve the compaction density of the negative electrode sheet and the cycle performance of the material. As an example, (Dv90-Dv10) / Dv50 can be but is not limited to 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3 or a range between any two of the above values.

[0142] In some optional embodiments, the particle size distribution Dv90 of the silicon-carbon composite material satisfies: 1≤(Dv90-Dv10) / Dv50≤2.

[0143] The Dv10, Dv50 and Dv90 of a material are well known in the art and can be measured by methods known in the art, for example, by referring to the standard GB / T 19077-2016 and using a laser particle size analyzer (such as Malvern Master Size 3000).

[0144] Among them, the physical definitions of Dv10, Dv50, and Dv90 are as follows:

[0145] Dv10: The particle size corresponding to when the cumulative volume distribution percentage of the material reaches 10%;

[0146] Dv50: The particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%;

[0147] Dv90: The particle size corresponding to when the cumulative volume distribution percentage of the material reaches 90%.

[0148] As a possible implementation method, the specific surface area of ​​the silicon-carbon composite material is 1m 2 / g-10m 2 When the specific surface area of ​​the silicon-carbon composite material is within the above range, it is beneficial to improve the efficiency of the secondary battery. As an example, the specific surface area of ​​the silicon-carbon composite material can be, but is not limited to, 1 m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g or the range between any two of the above values.

[0149] In some optional embodiments, the specific surface area of ​​the silicon-carbon composite material is 2 m 2 / g-6m 2 / g.

[0150] As an example, the pore size of the pore structure of the carbon matrix and the specific surface area of ​​the silicon-carbon composite material mentioned above are well-known in the art and can be tested by methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method with reference to GB / T 19587-2017, and calculated by BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0151] In some embodiments, the tap density of the silicon-carbon composite material is 0.8 g / cm 3 -1.2g / cm 3 As an example, the tap density of the silicon-carbon composite material may be, but is not limited to, 0.8 g / cm 3 , 0.83g / cm 3 , 0.85g / cm 3 , 0.87g / cm 3 , 0.9g / cm 3 、0.92g / cm 3 , 0.95g / cm 3 、0.98g / cm 3 , 1g / cm 3 , 1.02g / cm 3 , 1.05g / cm 3 , 1.08g / cm 3 , 1.1g / cm 3 , 1.12g / cm 3 , 1.15g / cm 3 , 1.18g / cm 3 , 1.2g / cm 3 Or the range between any two of the above values.

[0152] In some optional embodiments, the tap density of the silicon-carbon composite material is 0.85 g / cm 3 -1.0g / cm 3 .

[0153] It should be noted that the tap density of the silicon-carbon composite material mentioned above refers to the mass per unit volume of the silicon-carbon composite material powder in a container after being tapped under specified conditions.

[0154] The tap density of the negative electrode active material is a well-known meaning in the art and can be tested by methods known in the art. For example, it can be measured using a powder tap density tester in accordance with the standard GB / T 5162-2006. For example, the FZS4-4B tap density tester of the Beijing Iron and Steel Research Institute is used, and the test parameters are as follows: vibration frequency: 250±15 times / min, amplitude: 3±0.2 mm, vibration number: 5000 times, and measuring cylinder: 25 mL.

[0155] In some embodiments, the powder resistivity of the silicon-carbon composite material at 16 MPa is ≤5Ω·cm. When the powder resistivity of the silicon-carbon composite material at 16 MPa is within the above range, the silicon-carbon composite material has excellent electrical conductivity, which helps to improve the kinetic performance of the battery. Optionally, the powder resistivity of the silicon-carbon composite material at 16 MPa is ≤2Ω·m. More optionally, the powder resistivity of the silicon-carbon composite material at 16 MPa is ≤1Ω·m.

[0156] As an example, the powder resistivity of the silicon-carbon composite material mentioned above at 16 MPa can be measured by the following method: place an appropriate amount of the sample to be tested in the feeding cup of the resistivity tester, apply pressure, manually collect data, and record the powder resistivity test results at different pressure points. The test pressure is 16 MPa.

[0157] In some embodiments, the mass proportion of silicon in the silicon-carbon composite material is 20%-60%. When the mass proportion of silicon in the silicon-carbon composite material is within the above range, the capacity, first efficiency and cycle performance of the silicon-carbon composite material can be improved. As an example, the mass proportion of silicon in the silicon-carbon composite material can be but not limited to 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range between any two of the above values.

[0158] In some optional embodiments, the mass proportion of silicon in the silicon-carbon composite material is 30%-50%. In some embodiments, at least part of the surface of the silicon-carbon composite material has a coating layer.

[0159] Optionally, the coating layer is a carbon coating layer; by providing the carbon coating layer, the conductivity of the material surface can be improved, which is helpful to maximize the capacity and improve the cycle performance of the silicon-carbon composite material. The carbon coating layer can also reduce the contact between the silicon-based material and the electrolyte, reduce battery side reactions, and improve the stability and safety of the material.

[0160] It should be noted that the carbon coating layer can be a continuous and complete coating layer or an incomplete coating layer; wherein "complete" means that the substance located on the inner side of the carbon coating layer is completely coated by the carbon coating layer, and the carbon coating layer completely isolates the substance on its inner side from the outer side. "Incomplete" means that the substance located on the inner side of the carbon coating layer is not completely coated by the carbon coating layer, and the substance on the inner side of the carbon coating layer can at least partially contact the outer side of the carbon coating layer. Preferably, the carbon coating layer is a continuous and complete coating layer.

[0161] In some optional embodiments, the material of the carbon coating layer includes amorphous carbon; the amorphous carbon can act as a fast-charging ion ring, improve the kinetic properties of the silicon-carbon composite material, and reduce the contact between the silicon-based material and the electrolyte.

[0162] In some optional embodiments, the thickness of the carbon coating layer is 50nm-200nm; for example, it can be but not limited to 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm or a range between any two of the above values. When the thickness of the carbon coating layer is higher than the above range, the capacity of the secondary battery may be reduced; when the thickness of the carbon coating layer is lower than the above range, the silicon-based material may be exposed, affecting the processing performance.

[0163] As an example, the thickness of the above-mentioned carbon coating layer can be measured using a transmission electron microscope.

[0164] In some embodiments, phosphorus element is distributed in the carbon matrix.

[0165] In some embodiments, at least one of aluminum and potassium is distributed in the carbon matrix.

[0166] The second aspect of the present application provides a method for preparing a silicon-carbon composite material, comprising the following steps:

[0167] The carbon material precursor is mixed with a phosphorus-containing compound and sintered to prepare a carbon matrix with a porous structure;

[0168] Silicon-based materials are deposited in the pore structure of a carbon matrix to prepare a silicon-carbon composite material.

[0169] It should be noted that the phosphorus-containing compound can be used as both a pore-forming additive and a phosphorus-doped raw material.

[0170] The present application provides a method for preparing a silicon-carbon composite material, which has a simple process, can achieve one-step pore formation, and the obtained pore size is relatively uniform, and phosphorus elements can be incorporated into the skeleton of the carbon matrix.

[0171] In some embodiments, mixing the carbon material precursor with the phosphorus-containing compound includes mixing the carbon material precursor with a solution containing the phosphorus-containing compound. Optionally, the solvent of the solution containing the phosphorus-containing compound is water.

[0172] In some optional embodiments, the carbon material precursor is mixed with the solution containing the phosphorus-containing compound and then allowed to stand; standing is conducive to the solution containing the phosphorus-containing compound infiltrating the carbon material precursor.

[0173] In some optional embodiments, the standing time is 12h-24h; for example, it can be but not limited to 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h or a range before any two of the above times.

[0174] In some embodiments, the phosphorus-containing compound includes one or more of phosphoric acid, potassium phosphate, sodium phosphate, monocalcium phosphate, and monopotassium phosphate.

[0175] As a possible implementation, the carbon material precursor includes one or more of biomass hard carbon and resin-based carbon materials.

[0176] Optionally, the biomass hard carbon includes one or more of coconut shell, lignin, bamboo powder and starch.

[0177] It should be noted that bamboo powder is a powder prepared using bamboo as raw material.

[0178] Optionally, the resinous carbon material includes one or more of phenolic resin, epoxy resin, urea-formaldehyde resin and furan resin.

[0179] In some embodiments, the carbon material precursor contains at least one of aluminum and potassium.

[0180] In some optional embodiments, the mass proportion of aluminum in the carbon material precursor is 5ppm-80ppm; for example, it can be but not limited to 5ppm, 10ppm, 15ppm, 20ppm, 25ppm, 30ppm, 35ppm, 40ppm, 45ppm, 50ppm, 55ppm, 60ppm, 65ppm, 70ppm, 75ppm, 80ppm or the range between any two of the above values. As an example, the mass proportion of aluminum in the carbon material precursor can be but not limited to 5ppm-75ppm, 10ppm-70ppm, 15ppm-65ppm, 20ppm-60ppm, 25ppm-55ppm, 30ppm-50ppm, 35ppm-45ppm, 10ppm-35ppm, 15ppm-30ppm or 20ppm-30ppm, etc. .

[0181] In some optional embodiments, the mass proportion of aluminum element in the carbon material precursor is 6ppm-60ppm.

[0182] In some optional embodiments, the carbon material precursor further contains potassium, and the mass proportion of potassium in the carbon material precursor is 5ppm-80ppm; for example, it can be but not limited to 5ppm, 7ppm, 10ppm, 13ppm, 15ppm, 17ppm, 20ppm, 23ppm, 25ppm, 27ppm, 30ppm, 33ppm, 35ppm, 37ppm, 40ppm, 43ppm, 45ppm, 47ppm, 50ppm, 53ppm, 55ppm, 57ppm, 60ppm, 63ppm, 65ppm, 67ppm, 70ppm, 73ppm, 75ppm, 77ppm, 80ppm or a range between any two of the above values.

[0183] As an example, the mass proportion of potassium in the carbon material precursor can be but is not limited to 5ppm-75ppm, 10ppm-70ppm, 15ppm-65ppm, 20ppm-60ppm, 25ppm-55ppm, 30ppm-50ppm, 35ppm-45ppm, 10ppm-35ppm, 15ppm-40ppm or 20ppm-35ppm, etc.

[0184] In some optional embodiments, the mass proportion of potassium in the carbon material precursor is 10ppm-70ppm.

[0185] In some embodiments, the mass ratio of the carbon precursor to the phosphorus-containing compound is 100:(3-15); for example, it can be but not limited to 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14, 100:15 or a range between any two of the above values. When the mass ratio of the carbon precursor to the phosphorus-containing compound is within the above range, the P element can be within the required range.

[0186] In some optional embodiments, the mass ratio of the carbon material precursor to the phosphoric acid substance is 100:(4-10).

[0187] In some embodiments, the sintering temperature is 600°C-1000°C; for example, it can be but not limited to 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or a range between any two of the above values. Optionally, the sintering temperature is 600°C-900°C.

[0188] In some embodiments, the sintering time is 1 h-12 h; for example, it can be but not limited to 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or a range between any two of the above values. Optionally, the sintering time is 4 h-8 h.

[0189] When the sintering temperature and time are controlled within the above ranges, if the treatment time is too long, the P element will be added beyond the requirement.

[0190] In some embodiments, the sintering process atmosphere includes one or more of an inert gas and nitrogen. Alternatively, the sintering process atmosphere includes one or more of argon and nitrogen.

[0191] As a possible implementation, the step of depositing the silicon-based material in the pore structure of the carbon matrix includes: placing the carbon matrix in a mixed gas containing a silicon source and a first protective gas, and performing a first vapor deposition to deposit the silicon-based material in the pore structure of the carbon matrix. The use of a vapor deposition method to deposit the silicon-based material in the pore structure can increase the proportion of the silicon-based material embedded in the pore structure.

[0192] In some optional embodiments, the temperature of the first vapor deposition is 400°C-800°C; for example, it can be but not limited to 400°C, 430°C, 450°C, 480°C, 500°C, 530°C, 550°C, 570°C, 600°C, 630°C, 650°C, 680°C, 700°C, 730°C, 750°C, 770°C, 800°C or the range between any two of the above values. When the temperature of the first vapor deposition is in the above range, it is beneficial to regulate the grain size of the silicon-based material to be within a suitable range. It can be 500°C-700°C, and more preferably 500°C-600°C.

[0193] In some optional embodiments, the time of the first vapor deposition is 1h-12h; for example, it can be but not limited to 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range between any two of the above values. It can be 4h-8h. The time of the first vapor deposition is within the above range, which is conducive to obtaining a silicon-based material with a suitable particle size and is conducive to regulating the silicon-based material to achieve a suitable mass proportion in the silicon-carbon composite material.

[0194] In some optional embodiments, the volume proportion of the silicon source in the mixed gas is 10%-50%.

[0195] In some optional embodiments, the volume proportion of the first protective gas in the mixed gas is 30%-85%.

[0196] As a possible implementation manner, the positive difference between the pressure of the first vapor deposition and the atmospheric pressure is 200Pa-600Pa; for example, it can be but not limited to 200Pa, 250Pa, 300Pa, 350Pa, 400Pa, 450Pa, 500Pa, 550Pa, 600Pa or a range between any two of the above values.

[0197] It should be noted that the positive difference refers to how much the pressure of the first vapor deposition is higher than the atmospheric pressure.

[0198] In some embodiments, the silicon source includes one or more of monosilane, disilane, and trisilane.

[0199] In some embodiments, the first protective gas includes one or more of nitrogen and argon.

[0200] In some embodiments, the mixed gas further includes a first carbon source, thereby promoting the decomposition of the silicon source.

[0201] In some optional embodiments, the volume proportion of the first carbon source in the mixed gas is 5%-20%.

[0202] In some optional embodiments, in some optional embodiments, the volume ratio of the silicon source to the first carbon source is (2-10):1; for example, it can be but not limited to 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or a range between any two of the above values. When the volume ratio of the silicon source to the first carbon source is higher than the above range, the carbon content decomposition ratio is high and the capacity improvement effect is general; when the volume ratio of the silicon source to the first carbon source is lower than the above range, the silicon-based material content on the surface of the carbon matrix will increase, and the slurry processing will have problems.

[0203] As a possible implementation manner, the first carbon source includes one or more of methane, ethylene and acetylene.

[0204] As a possible implementation manner, after the step of depositing the silicon-based material in the pore structure of the carbon matrix, the method further includes:

[0205] The carbon substrate is placed in a mixed gas containing a second carbon source and a second protective gas, and a second vapor deposition is performed to form a carbon coating layer on at least a portion of the outer surface of the carbon substrate. The carbon coating layer is prepared by vapor deposition, which facilitates the regulation of the coating amount to improve the surface conductivity of the silicon-carbon composite material, helps to exert the material capacity, and helps to maintain the stability and safety of the silicon-carbon composite material.

[0206] In some optional embodiments, the temperature of the second vapor deposition is 500℃-900℃; for example, it can be but is not limited to 500℃, 530℃, 550℃, 580℃, 600℃, 630℃, 650℃, 680℃, 700℃, 730℃, 750℃, 770℃, 800℃, 830℃, 850℃, 880℃, 900℃ or a range between any two of the above values.

[0207] In some optional embodiments, the time of the second vapor deposition is 1 h-6 h; for example, it can be but is not limited to 1 h, 2 h, 3 h, 4 h, 5 h, 6 h or a range between any two of the above values.

[0208] In some optional embodiments, the volume proportion of the second carbon source in the mixed gas is 5%-50%, and the sum of the volume proportions of the second carbon source and the second protective gas in the mixed gas is 100%.

[0209] In some alternative embodiments, the second carbon source includes one or more of methane, ethylene and acetylene.

[0210] In some optional embodiments, the second protective gas includes one or more of nitrogen and argon.

[0211] It should be noted that the above-mentioned “first carbon source”, “second carbon source”, “first protective gas”, “second protective gas”, “first vapor deposition” and “second vapor deposition” are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features.

[0212] In some embodiments, the method for preparing the silicon-carbon composite material comprises the following steps:

[0213] The carbon precursor is mixed with a solution containing a phosphorus-containing compound and then allowed to stand for 12h-24h, and then sintered to prepare a carbon matrix with a porous structure. The phosphorus-containing compound includes one or more of phosphoric acid, potassium phosphate, sodium phosphate, calcium dihydrogen phosphate and potassium dihydrogen phosphate. The carbon precursor includes one or more of biomass hard carbon and resin-type carbon materials, the biomass hard carbon includes one or more of coconut shell, lignin, bamboo powder and starch, and the resin-type carbon material includes one or more of phenolic resin, epoxy resin, urea-formaldehyde resin and furan resin. The mass ratio of the carbon precursor and the phosphorus-containing compound is 100:(3-15), and can be optionally 100:(4-10). The carbon precursor contains at least one of aluminum and potassium; the mass proportion of aluminum in the carbon precursor is 5ppm-80ppm; it can be optionally 6ppm-60ppm; the mass proportion of potassium in the carbon precursor is 5ppm-80ppm; it can be optionally 6ppm-60ppm. The temperature of the sintering treatment is 600°C-1000°C, and can be 600°C-900°C. The time of the sintering treatment is 1h-12h, and can be 4h-8h. The atmosphere of the sintering treatment includes one or more of argon and nitrogen.

[0214] The carbon matrix is ​​placed in a mixed gas containing a silicon source, a first carbon source and a first protective gas, and a first vapor deposition is performed to deposit a silicon-based material in the pore structure of the carbon matrix. The temperature of the first vapor deposition is 400°C-800°C, optionally 500°C-700°C, and more optionally 500°C-600°C. The time of the first vapor deposition is 1h-12h, optionally 4h-8h. The volume proportion of the silicon source in the mixed gas is 10%-50%, the volume proportion of the first carbon source in the mixed gas is 5%-20%, the volume proportion of the first protective gas in the mixed gas is 30%-85%, and the sum of the volume proportions of the silicon source, the first carbon source and the first protective gas in the mixed gas is 100%; the volume ratio of the silicon source to the first carbon source is (2-10): 1. The positive difference between the pressure of the first vapor deposition and the atmospheric pressure is 200Pa-600Pa. The silicon source includes one or more of monosilane, disilane and trisilane. The first carbon source includes one or more of methane, ethylene and acetylene. The first protective gas includes one or more of nitrogen and argon.

[0215] The carbon substrate after the deposition of the silicon-based material is placed in a mixed gas containing a second carbon source and a second protective gas, and a second vapor deposition is performed to form a carbon coating layer on at least part of the outer surface of the carbon substrate. The temperature of the second vapor deposition is 500°C-900°C. The time of the second vapor deposition is 1h-6h. The volume proportion of the second carbon source in the mixed gas is 5%-50%, and the sum of the volume proportions of the second carbon source and the second protective gas in the mixed gas is 100%. The second carbon source includes one or more of methane, ethylene and acetylene. The second protective gas includes one or more of nitrogen and argon.

[0216] The third aspect of the present application provides a negative electrode plate, including a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer includes the silicon-carbon composite material of the first aspect of the present application or the silicon-carbon composite material prepared by the method of the second aspect of the present application.

[0217] The negative electrode plate of the present application comprises the silicon-carbon composite material provided in the present application, and its volume conversion rate during the charge and discharge process is significantly reduced.

[0218] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0219] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0220] In some of the embodiments, the negative electrode active material may also adopt the negative electrode active material for batteries known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon nitrogen complexes, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0221] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0222] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0223] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0224] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt% to 60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000-10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75g / m 2 -220 g / m 2 The compaction density of the negative electrode sheet can be 1.3g / cm 3 -1.8g / cm 3 .

[0225] The fourth aspect of the present application provides a secondary battery, comprising the negative electrode sheet of the third aspect of the present application.

[0226] The secondary battery of the present application comprises the silicon-carbon composite material provided by the present application and has excellent cycle performance.

[0227] In addition, the secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0228] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0229] Positive electrode

[0230] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.

[0231] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0232] In some of the embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0233] The positive electrode active material may be a positive electrode active material for a secondary battery known in the art.

[0234] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material for the lithium-ion battery may include, but is not limited to, one or more of lithium-containing transition metal oxides and lithium-containing phosphates. Examples of the lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or their respective modified compounds. Examples of the lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, or their respective modified compounds.

[0235] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium-ion battery may include Li a Ni b Co c M d O e A f , where 0.5 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M includes one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A includes one or more of N, F, S, and Cl.

[0236] In some embodiments, by way of example, the positive electrode active material for the lithium-ion battery may include LiCoO 2 , LiNiO 2 , LiMnO 2 , LiMn 2 O 4 , LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O 2 , LiFePO4 and LiMnPO 4 One or more of .

[0237] In the present application, the modified compound of each positive electrode active material mentioned above may be a compound obtained by doping and / or surface coating the positive electrode active material.

[0238] In some of these embodiments, the positive electrode active material layer may also optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0239] In some embodiments, the positive electrode active material layer may further include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0240] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector.

[0241] Electrolytes

[0242] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0243] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0244] In some embodiments, the electrolyte salt may include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO 2 F 2 ), one or more of lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorooxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0245] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, ), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate One or more of fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0246] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0247] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.

[0248] Isolation film

[0249] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0250] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0251] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.

[0252] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0253] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0254] The secondary battery includes at least one battery cell. The secondary battery may include one or more battery cells.

[0255] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.

[0256] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0257] In some of these embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs.

[0258] The secondary battery may be a battery module 4 or a battery pack 1 .

[0259] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.

[0260] Figure 3 4 is an example of a battery module. Figure 3In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0261] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0262] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.

[0263] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0264] In addition, the present application also provides an electrical device, which includes a secondary battery provided by the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.

[0265] As an electrical device, a secondary battery can be selected according to its usage requirements.

[0266] Figure 6 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0267] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0268] Example

[0269] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If the techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0270] 1. Preparation of silicon-carbon composite materials

[0271] Example 1

[0272] Take 1 kg of bamboo powder (as a carbon precursor), add 0.3 kg of a 10 wt% phosphoric acid solution (as a phosphoric acid substance), use a VC mixer to mix evenly, let it stand for 24 hours, then increase the temperature to 800 ° C at a rate of 5 ° C / min, keep warm for 4 hours, and obtain a carbon matrix with a porous structure. After the furnace is cooled, take it out for use; wherein, the mass ratio of the carbon precursor and the phosphoric acid substance is 100:5; the mass proportion of aluminum in the carbon precursor is 60 ppm, and the mass proportion of potassium is 65 ppm; the average pore size of the carbon matrix is ​​1.8 nm, the number of micropores accounts for 80%, the number of mesopores accounts for 20%, and the specific surface area of ​​the carbon matrix is ​​1600 m 2 / g;

[0273] The carbon substrate was placed in a fluidized bed deposition furnace, and the temperature was raised to 500°C at a heating rate of 5°C / min. A mixed gas of monosilane (as a silicon source) and nitrogen (as a first protective gas) was introduced at a volume ratio of 2:8, with a total gas flow rate of 5 L / min. The pressure in the furnace was controlled to be slightly higher than the atmospheric pressure by 200 Pa, and the deposition was performed for 4 hours.

[0274] Stop introducing monosilane, continue to raise the temperature to 600°C, introduce a mixed gas of acetylene (as the second carbon source) and nitrogen (as the second protective gas) in a volume ratio of 4:6, and deposit for 2 hours. After cooling, discharge and sieve to obtain a silicon-carbon composite material. In the silicon-carbon composite material, the silicon-based material (elemental silicon) is deposited in the pore structure of the carbon matrix. The mass proportion of silicon in the silicon-carbon composite material is about 50%, the content of phosphorus is about 4ppm, the content of aluminum is about 30ppm, the content of potassium is about 32ppm, the size of the deposited silicon grains is about 2nm, and the volume distribution particle size Dv50 of the silicon-carbon composite material is about 7.8μm.

[0275] The preparation methods of Examples 2-9 are similar to those of Example 1, and the differences are detailed in Table 1.

[0276] Comparative Example 1

[0277] 1 kg of phenolic resin (as a carbon material precursor) was mixed with 0.93 kg of a 15 wt% KOH solution, and then sintered under a nitrogen atmosphere at a heating rate of 1 ° C / min, a heat treatment temperature of 800 ° C, and kept warm for 4 hours. After cooling, the carbon matrix was washed with water to remove impurities and dried to obtain a carbon matrix for standby use;

[0278] The carbon substrate was placed in a fluidized bed deposition furnace, and the temperature was raised to 500°C at a heating rate of 5°C / min. A mixed gas of monosilane (as a silicon source) and nitrogen (as a first protective gas) was introduced at a volume ratio of 2:8, with a total gas flow rate of 5 L / min. The pressure in the furnace was controlled to be slightly higher than the atmospheric pressure by 200 Pa, and the deposition was performed for 4 hours.

[0279] Stop introducing monosilane, continue to raise the temperature to 600°C, introduce a mixed gas of acetylene (as the second carbon source) and nitrogen (as the second protective gas) in a volume ratio of 4:6, and deposit for 2 hours. After cooling, discharge the material and sieve through 325 mesh to obtain a silicon-carbon composite material.

[0280] Comparative Example 2

[0281] The preparation methods of Comparative Example 2 and Example 1 are similar, except that no phosphorus source is added when preparing the carbon matrix. The specific preparation method is as follows: Take 1 kg of bamboo powder (as a carbon material precursor), the mass proportion of aluminum element in the carbon material precursor is 60 ppm, and the mass proportion of potassium element is 65 ppm; add 340 g of KOH solid, use a VC mixer to mix evenly, let stand for 24 hours, then increase the temperature to 800 ° C at a rate of 5 ° C / min, keep warm for 4 hours, and obtain a carbon matrix with a porous structure. After the furnace is cooled, take it out for use;

[0282] The carbon substrate was placed in a fluidized bed deposition furnace, and the temperature was raised to 500°C at a heating rate of 5°C / min. A mixed gas of monosilane (as a silicon source) and nitrogen (as a first protective gas) was introduced at a volume ratio of 2:8, with a total gas flow rate of 5 L / min. The pressure in the furnace was controlled to be slightly higher than the atmospheric pressure by 200 Pa, and the deposition was performed for 4 hours.

[0283] Stop introducing monosilane, continue to raise the temperature to 600°C, introduce a mixed gas of acetylene (as the second carbon source) and nitrogen (as the second protective gas) in a volume ratio of 4:6, and deposit for 2 hours. After cooling, discharge the material and sieve it to obtain a silicon-carbon composite material.

[0284] The parameter settings in the above embodiments are shown in Table 1.

[0285] Table 1

[0286]

[0287] The phosphorus content, potassium content, aluminum content, silicon grain size and volume distribution particle size Dv50 of the silicon-carbon composite materials prepared in the above embodiments and comparative examples were measured. The results are shown in Table 2.

[0288] It should be noted that the phosphorus content, aluminum content and potassium content in the above-mentioned silicon-carbon composite materials are determined by the following method: 0.5 g of silicon-carbon composite material sample is subjected to microwave digestion with 10 mL of nitric acid and 10 mL of hydrofluoric acid, added to a 50 mL volumetric flask after digestion to make up the volume, and then the content of the target element is determined by ICAP-7000 ICP-OES.

[0289] The grain size of the silicon-based materials mentioned above was characterized by transmission electron microscopy.

[0290] The volume distribution particle size Dv50 of the silicon-carbon composite material mentioned above is measured by using a laser particle size analyzer Malvern Master Size 3000 with reference to the standard GB / T 19077-2016.

[0291] 2. Preparation of secondary battery (full battery)

[0292] 1. Negative electrode

[0293] The silicon-carbon composite material prepared above, the conductive agent carbon nanotube and SP mixture, the binder styrene-butadiene rubber, and the thickener sodium carboxymethyl cellulose were fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 95.5:1:2:1.5 to form a negative electrode slurry. The negative electrode slurry was coated on both surfaces of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet was obtained.

[0294] 2. Positive electrode

[0295] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811) was mixed with conductive carbon black and polyvinylidene fluoride in a weight ratio of 97.5:1.2:1.3, and an appropriate amount of solvent NMP was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.

[0296] 3. Electrolyte:

[0297] A mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) was used as an organic solvent, wherein the volume ratio of EC, EMC and DEC was 20%:20%:60%. In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt (LiPF6) was dissolved in the above organic solvent, and an additive fluoroethylene carbonate (FEC) was added to obtain an electrolyte. In the electrolyte, LiPF 6 The concentration is 1 mol / L, and the mass proportion of FEC in the electrolyte is 5%.

[0298] 4. Isolation film

[0299] Polypropylene film is used as the isolation membrane.

[0300] 5. Preparation of Secondary Batteries

[0301] Place the isolation film and the positive electrode sheet and negative electrode sheet prepared above in order, so that the isolation film is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wind to obtain an electrode assembly; place the electrode assembly in an outer package, inject the above-prepared electrolyte after drying, and obtain a secondary battery after vacuum packaging, standing, formation, capacity and other processes.

[0302] 3. Battery performance test

[0303] 1. Cycle performance test

[0304] At 25°C, the secondary battery prepared above was charged to 4.25V at 0.5C, and then discharged to 2.5V at 1C. This is a cycle charge and discharge process, and the discharge capacity at this time is recorded as the initial discharge capacity. The secondary battery was further subjected to the cycle charge and discharge test according to the above method, and the discharge capacity after each cycle was recorded until the discharge capacity of the secondary battery decayed to 80% of the initial discharge capacity, and the number of cycles at this time was recorded. The results are shown in Table 2.

[0305] Table 2

[0306]

[0307] The sintering temperature in Table 1 refers to the holding temperature when preparing the carbon matrix, and the sintering time refers to the holding time when preparing the carbon matrix.

[0308] From the comparison of the results of Examples 1-29 and Comparative Examples 1-2, it can be seen that the silicon-carbon composite material with a specific structure of the present application contains phosphorus, which effectively improves the cycle performance of the battery.

[0309] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced to each other, and for the sake of brevity, they will not be repeated herein.

[0310] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A silicon-carbon composite material, characterized in that: include: A carbon matrix having a porous structure; as well as A silicon-based material distributed in the pore structure of the carbon matrix; The silicon-carbon composite material contains phosphorus element.

2. The silicon-carbon composite material according to claim 1, characterized in that: The mass proportion of the phosphorus element in the silicon-carbon composite material is 5ppm-80ppm; optionally 10ppm-50ppm.

3. The silicon-carbon composite material according to any one of claims 1 to 2, characterized in that: The silicon-carbon composite material further contains at least one of aluminum and potassium; Optionally, the silicon-carbon composite material further contains aluminum, and the mass proportion of phosphorus in the silicon-carbon composite material is greater than the mass proportion of aluminum in the silicon-carbon composite material; Optionally, the silicon-carbon composite material further contains potassium, and the mass proportion of phosphorus in the silicon-carbon composite material is greater than the mass proportion of potassium in the silicon-carbon composite material; Optionally, the silicon-carbon composite material further contains aluminum and potassium, and the mass proportion of the aluminum in the silicon-carbon composite material is less than the mass proportion of the potassium in the silicon-carbon composite material; Optionally, the silicon-carbon composite material further contains aluminum element, and the mass proportion of the aluminum element in the silicon-carbon composite material is 5ppm-80ppm; optionally 10ppm-40ppm; Optionally, the silicon-carbon composite material further contains potassium element, and the mass proportion of the potassium element in the silicon-carbon composite material is 5ppm-80ppm; optionally 10ppm-70ppm.

4. The silicon-carbon composite material according to any one of claims 1 to 3, characterized in that: The silicon-based material has one or more of the following characteristics: (1) The grain size of the silicon-based material is ≤8nm, and may be ≤5nm, and may be 1nm-4nm; (2) The silicon-based material includes one or more of silicon, silicon-oxygen compounds, silicon-carbon compounds or silicon alloys; (3) The shape of the silicon-based material includes one or more of spherical, quasi-spherical, flake and linear.

5. The silicon-carbon composite material according to any one of claims 1 to 4, characterized in that: The carbon matrix has one or more of the following characteristics: (1) The average pore size of the pore structure is 0.5 nm-8 nm, and can be 0.5 nm-5 nm; (2) The pore structure includes micropores, and the average pore diameter d1 of the micropores satisfies: 0.5 nm ≤ d1 < 2 nm; (3) The pore structure includes mesopores, and the average pore diameter d2 of the mesopores satisfies: 2nm≤d2≤8nm; (4) The pore structure includes micropores, and the number of the micropores in the pore structure accounts for 60%-90%, and can be 70%-80%; (5) The specific surface area of ​​the carbon matrix is ​​500 m 2 / g-2000m 2 / g, optional 1000m 2 / g-1800m 2 / g.

6. The silicon-carbon composite material according to any one of claims 1 to 5, characterized in that: The silicon-carbon composite material has one or more of the following characteristics: (1) The volume distribution particle size Dv50 of the silicon-carbon composite material is 3 μm-15 μm, and can be optionally 5 μm-12 μm; (2) The volume distribution particle size Dv90 of the silicon-carbon composite material is ≤35 μm, which can be selected to be 15 μm-25 μm; (3) The particle size distribution of the silicon-carbon composite material satisfies: 1≤(Dv90-Dv10) / Dv50≤3, which may be 1≤(Dv90-Dv10) / Dv50≤2; (4) The specific surface area of ​​the silicon-carbon composite material is 1 m 2 / g-10m 2 / g, optional 2m 2 / g-6m 2 / g; (5) The tap density of the silicon-carbon composite material is 0.8 g / cm 3 -1.2g / cm 3 , optional 0.85g / cm 3 -1.0g / cm 3 ; (6) The powder resistivity of the silicon-carbon composite material at 16 MPa is ≤5Ω·cm, and can be ≤2Ω·cm; (7) The mass proportion of silicon element in the silicon-carbon composite material is 20%-60%, and can be optionally 30%-50%.

7. The silicon-carbon composite material according to any one of claims 1 to 6, characterized in that: At least part of the surface of the silicon-carbon composite material has a coating layer; optionally, the coating layer is a carbon coating layer.

8. The silicon-carbon composite material according to claim 7, characterized in that: The carbon coating layer has one or more of the following characteristics: (1) The material of the carbon coating layer includes amorphous carbon; (2) The thickness of the carbon coating layer is 50nm-200nm.

9. The silicon-carbon composite material according to claim 7, characterized in that: The phosphorus element is distributed in the carbon matrix; and / or at least one of the aluminum element and the potassium element is distributed in the carbon matrix.

10. A method for preparing the silicon-carbon composite material according to any one of claims 1 to 9, characterized in that: The steps include: The carbon material precursor is mixed with a phosphorus-containing compound and sintered to prepare a carbon matrix with a porous structure; The silicon-based material is deposited in the pore structure of the carbon matrix to prepare the silicon-carbon composite material.

11. The method for preparing the silicon-carbon composite material according to claim 10, characterized in that: The mass ratio of the carbon material precursor to the phosphorus-containing compound is 100:(3-15); or optionally 100:(4-10).

12. The method for preparing the silicon-carbon composite material according to any one of claims 10 to 11, characterized in that: The sintering temperature is 600°C-1000°C; optionally 600°C-900°C.

13. The method for preparing the silicon-carbon composite material according to any one of claims 10 to 12, characterized in that: The sintering time is 1h-12h; optionally 4h-8h.

14. The method for preparing the silicon-carbon composite material according to any one of claims 10 to 13, characterized in that: The conditions for preparing the carbon matrix also include one or more of the following conditions: (1) Mixing the carbon material precursor with the phosphorus-containing compound includes mixing the carbon material precursor with a solution containing the phosphorus-containing compound; Optionally, the carbon material precursor is mixed with a solution containing the phosphorus-containing compound and then allowed to stand; Further optionally, the standing time is 12h-24h; (2) the phosphorus-containing compound includes one or more of phosphoric acid, potassium phosphate, sodium phosphate, monocalcium phosphate or monopotassium phosphate; (3) The carbon material precursor includes one or more of biomass hard carbon or resin-based carbon materials; (4) The carbon material precursor contains at least one of aluminum and potassium; Optionally, the carbon material precursor contains aluminum element, and the mass proportion of the aluminum element in the carbon material precursor is 5ppm-80ppm; optionally 6ppm-60ppm; Optionally, the carbon material precursor contains potassium element, and the mass proportion of the potassium element in the carbon material precursor is 5ppm-80ppn; optionally 6ppm-60ppm; (5) The sintering atmosphere includes one or more of an inert gas and nitrogen; Optionally, the atmosphere of the sintering process includes one or more of argon and nitrogen.

15. The method for preparing the silicon-carbon composite material according to any one of claims 10 to 14, characterized in that: The step of depositing the silicon-based material in the pore structure of the carbon matrix comprises: Placing the carbon substrate in a mixed gas containing a silicon source and a first protective gas, and performing a first vapor deposition to deposit the silicon-based material in the pore structure of the carbon substrate; Optionally, the first vapor deposition comprises one or more of the following conditions: (1) The temperature of the first vapor deposition is 400° C.-800° C., optionally 500° C.-700° C., and more preferably 500° C.-600° C.; (2) The time of the first vapor deposition is 1 h to 12 h, and can be 4 h to 8 h; (3) The volume proportion of the silicon source in the mixed gas is 10%-50%; (4) The volume proportion of the first protective gas in the mixed gas is 30%-85%; (5) The positive difference between the pressure of the first vapor deposition and the atmospheric pressure is 200Pa-600Pa; (6) The silicon source includes one or more of monosilane, disilane and trisilane; (7) The first protective gas includes one or more of nitrogen and argon.

16. The method for preparing the silicon-carbon composite material according to any one of claims 10 to 15, characterized in that: The mixed gas also includes a first carbon source; Optionally, the volume proportion of the first carbon source in the mixed gas is 5%-20%; Optionally, the volume ratio of the silicon source to the first carbon source is (2-10):1; Optionally, the first carbon source includes one or more of methane, ethylene and acetylene.

17. The method for preparing the silicon-carbon composite material according to any one of claims 10 to 16, characterized in that: After the step of depositing the silicon-based material in the pore structure of the carbon matrix, the method further comprises: Placing the carbon substrate in a mixed gas containing a second carbon source and a second protective gas, and performing a second vapor deposition to form the carbon coating layer on at least a portion of the outer surface of the carbon substrate; Optionally, the second vapor deposition comprises one or more of the following conditions: (1) The temperature of the second vapor deposition is 500° C.-900° C.; (2) The second vapor deposition time is 1h-6h; (3) the volume proportion of the second carbon source in the mixed gas is 5%-50%, and the sum of the volume proportions of the second carbon source and the second protective gas in the mixed gas is 100%; (4) the second carbon source includes one or more of methane, ethylene and acetylene; (5) The second protective gas includes one or more of nitrogen and argon.

18. A negative electrode plate, characterized in that: include: Anode current collector; as well as A negative electrode active material layer is located on at least one side of the negative electrode current collector, and the negative electrode active material layer comprises the silicon-carbon composite material according to any one of claims 1 to 9 or the silicon-carbon composite material prepared by the method according to any one of claims 10 to 17.

19. A secondary battery, characterized in that: Comprising the negative electrode sheet as described in claim 18.

20. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 19.

Citation Information

Patent Citations

  • Method for purifying plant-derived carbon precursor

    CN106794989A

  • A phosphorus-doped carbon-coated Na3V2 (PO4)2O2F cathode material and a preparation method thereof

    CN109037630A

  • Negative electrode material and preparation method thereof, battery and terminal

    CN112838197A

  • Three-dimensional porous silicon-carbon composite material and preparation method and application thereof

    CN113078318A

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN114068901A

Cited By

  • Silicon-carbon material, preparation method thereof, secondary battery and electric device

    CN119833588A

  • Negative plate and battery

    CN121709535A

  • Silicon-carbon composite material and preparation method therefor, negative electrode sheet, secondary battery, and device

    EP4819230A1